A polydopamine-coated copper-doped hydroxyapatite material and a method for preparing the same

CN117599241BActive Publication Date: 2026-10-27ASIA BIOMATERIALS WUHAN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311549318.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2026-10-27
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

然而,纯HAp的降解速率慢,在植入后往往会被新生成的骨覆盖,不能介导新的血管生成或组织长入,阻碍材料的降解和吸收

Benefits of technology

[0024](1)本发明将铜离子(Cu2+)掺杂到羟基磷灰石中,并配合聚多巴胺的包覆,获得的涂覆聚多巴胺掺铜羟基磷灰石材料,具有优异的光热响应能力,具有良好的生物相容性,且能缓慢并长时间释放Cu2+,有利于组织修复,并能起到抑菌作用,且诱导血管再生和骨组织生长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004559143960000081
    Figure BDA0004559143960000081
  • Figure BDA0004559143960000091
    Figure BDA0004559143960000091
  • Figure BDA0004559143960000101
    Figure BDA0004559143960000101
Patent Text Reader

Abstract

The application belongs to the technical field of biological materials, and provides a kind of coated polydopamine copper-doped hydroxyapatite material and preparation method.It is composed of copper-doped hydroxyapatite and polydopamine coated on the surface of copper-doped hydroxyapatite, and copper is doped into HAp crystal lattice by replacing calcium in the copper-doped hydroxyapatite, and the copper doping amount is 1% to 10% by mass percentage.Copper ions are doped into hydroxyapatite in the application, and polydopamine is coated, to obtain a coated polydopamine copper-doped hydroxyapatite material, which has excellent photothermal response ability, good biocompatibility, and can slowly and long-term release Cu 2+ , is beneficial to tissue repair, can play a role in inhibiting bacteria, and can induce blood vessel regeneration and bone tissue growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomaterials technology, and in particular to a polydopamine-coated copper-doped hydroxyapatite material and its preparation method. Background Technology

[0002] Photothermal therapy (PTT) is a promising method for treating bacterial infections, cancer, and tumors due to its non-invasiveness, high controllability, and precision. Near-infrared light is less absorbed and scattered by tissues, allowing for deeper tissue penetration. Furthermore, PTT exhibits significant antibacterial activity, promotes angiogenesis, and enhances the local immune system response. Simultaneously, gentle local heating can promote the expression of various genes involved in tissue repair, thereby promoting cell proliferation and differentiation, ultimately accelerating tissue regeneration.

[0003] Bones, as the framework of the human body, provide support and protection. However, in daily life, people often experience bone fractures or even defects due to improper exercise or external mechanical forces. Hydroxyapatite (HAp,(Ca) 10 The chemical composition of hydroxyapatite (HAp) is the same as that of the main inorganic mineral components of human bone tissue. Due to its good biocompatibility, osteoconductivity, and osteoinductive properties, it is widely used for bone defect repair. However, pure HAp degrades slowly and is often covered by newly formed bone after implantation, failing to mediate new angiogenesis or tissue ingrowth, thus hindering material degradation and absorption. Furthermore, the bone defect repair process often carries the risk of bacterial infection. For example, patent CN 105664251B discloses an ultra-micro silver-doped hydroxyapatite coating and its preparation method, which achieves antibacterial effects through silver ion release or contact with the body, but its safety is difficult to guarantee.

[0004] Copper (Cu) is an essential trace element for humans and animals, enhancing the activity of various enzymes. Cu deficiency reduces the activity of important enzymes in the body, leading to impaired bone formation and osteoporosis. Studies have reported that Cu... 2+ Cu promotes angiogenesis and enhances the expression of vascular-related genes (vascular epithelial growth factor (VEGF)). When the concentration of Cu is between 14.2 and 152.7 ppm, it can significantly enhance the secretion of VEGF and alkaline phosphatase (ALP) by human bone marrow stromal cells (hBMSCs), thereby inducing the differentiation of mesenchymal stem cells and osteoblasts. In addition, Cu also has good antibacterial properties; it inhibits bacterial DNA proliferation by directly contacting bacteria, damaging their DNA, and affecting their metabolism.

[0005] Therefore, developing a Ca-P biomaterial with good biocompatibility and both photothermal response and antibacterial properties has important application value. Summary of the Invention

[0006] To address the aforementioned problems, the present invention aims to provide a polydopamine-coated copper-doped hydroxyapatite material and its preparation method, which combines photothermal response and antibacterial properties, exhibits good biocompatibility, and can slowly and continuously release a certain concentration of Cu. 2+ It can be used for tissue repair, such as for treating chronic bone infections and repairing defects.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a copper-doped hydroxyapatite coated with polydopamine, which is composed of copper-doped hydroxyapatite and polydopamine coated on the surface of copper-doped hydroxyapatite. In the copper-doped hydroxyapatite, copper replaces calcium and is doped into the HAp lattice. The amount of copper doping is 1% to 10% by mass percentage, that is, copper accounts for 1-10 wt% of the total mass of copper and calcium in the copper-doped hydroxyapatite.

[0009] According to the above scheme, hydroxyapatite (HAp) exhibits a nanoscale rod-like structure with a width of 10-40 nm and a length of 30-200 nm, and the copper doping content is preferably 1%-5%, more preferably 3%-5%.

[0010] According to the above scheme, polydopamine is formed on the surface of copper-doped hydroxyapatite by oxidative self-polymerization of dopamine, and polydopamine-coated copper-doped hydroxyapatite is obtained. The mass ratio of copper-doped hydroxyapatite to dopamine is 1:1 to 1:0.01, and the reaction conditions are: room temperature, light-proof, high-speed stirring for 8 to 24 hours.

[0011] According to the above scheme, the mass ratio of copper-doped hydroxyapatite to dopamine is preferably 1:0.1 to 1:0.01, more preferably 1:0.05 to 1:0.01, and even more preferably 1:0.05 to 0.02.

[0012] According to the above scheme, the copper content in the polydopamine-coated copper hydroxyapatite material is 3% to 5%, and the mass ratio of copper hydroxyapatite to dopamine is 1:0.05 to 1:0.02.

[0013] According to the above scheme, by adjusting the proportion of polydopamine coating, the temperature rise of the polydopamine-coated copper hydroxyapatite material after near-infrared irradiation can be controlled within 3 to 35°C.

[0014] According to the above scheme, the copper ion release concentration of the coated polydopamine-doped copper hydroxyapatite material of the present invention can reach more than 14.2 ppm, more preferably 20 to 100 ppm, and can be maintained for more than 72 hours, and most preferably more than one week.

[0015] Secondly, the present invention provides a method for preparing a polydopamine-coated copper-doped hydroxyapatite material, specifically comprising the following steps:

[0016] S1. Prepare copper-doped hydroxyapatite for later use;

[0017] S2. The copper-doped hydroxyapatite obtained in step S1 is mixed with a dopamine solution at a preset mass ratio. Polydopamine is formed on the surface of the copper-doped hydroxyapatite using an oxidative self-polymerization method with dopamine, thereby obtaining copper-doped hydroxyapatite coated with polydopamine.

[0018] As a further improvement of the present invention, the preparation method of copper-doped hydroxyapatite in step S1 includes the following steps: preparing calcium chloride and copper chloride dihydrate solutions for later use; preparing diammonium hydrogen phosphate solutions for later use; stirring and heating the prepared calcium chloride and copper chloride dihydrate solutions to 80-85°C, then adding acid to adjust the pH of the system to 3-5, and stirring thoroughly to obtain a mixed solution; adding the prepared diammonium hydrogen phosphate solution dropwise to the above-obtained reaction solution, mixing according to the preset (Ca+Cu) / P ratio, and stirring for 2-4 hours; then adding ammonia water dropwise to the reaction solution to adjust the pH to about 9-11, and continuing to stir for 0.5-1.5 hours, turning off the stirring and heating, and allowing the reaction solution to stand and age for at least 12 hours; collecting the precipitate, washing it repeatedly, then drying it at 50-100°C to constant weight, grinding and sieving to obtain copper-doped hydroxyapatite (CuHAp).

[0019] As a further improvement of the present invention, in step S1, the molar ratio is 1.65≤Ca / P≤1.82.

[0020] As a further improvement of the present invention, in step S2, the mass ratio of copper-doped hydroxyapatite to dopamine is 1:1 to 1:0.01, and the reaction conditions are: high-speed stirring at room temperature in the dark for 8 to 24 hours; the preparation method of the coated polydopamine-doped copper hydroxyapatite specifically includes the following steps: preparing a Tris solution and adjusting the pH value to 8.0 to 9.5 with dilute hydrochloric acid; adding dopamine to the prepared Tris solution and mechanically stirring at room temperature in the dark until the solution turns black; adding copper-doped hydroxyapatite to the above-obtained reaction solution and mixing according to the mass ratio of copper-doped hydroxyapatite to dopamine of 1:1 to 1:0.01, and stirring at room temperature in the dark for 8 to 24 hours; collecting the precipitate, washing repeatedly, then freeze-drying, grinding and sieving to obtain coated polydopamine-doped copper hydroxyapatite (PDA). x @CuHAp).

[0021] As a further improvement of the present invention, in step S1, the concentration of calcium ions in the calcium salt solution is 0.05-0.5 mol / L, the concentration of copper ions in the copper salt solution is 0.01-0.1 mol / L, and the concentration of phosphate ions in the phosphate salt solution is 0.03-0.35 mol / L.

[0022] As a further improvement of the present invention, in step S2, the mass ratio of copper-doped hydroxyapatite to dopamine is preferably 1:0.1 to 1:0.01, more preferably 1:0.05 to 1:0.01, and even more preferably 1:0.05 to 0.02.

[0023] The beneficial effects of this invention are:

[0024] (1) This invention utilizes copper ions (Cu) 2+ Copper-doped hydroxyapatite, combined with polydopamine coating, yields a polydopamine-coated copper-doped hydroxyapatite material exhibiting excellent photothermal response, good biocompatibility, and the ability to slowly and continuously release Cu. 2+ It is beneficial for tissue repair, has an antibacterial effect, and induces angiogenesis and bone tissue growth.

[0025] In this invention, Cu is used 2+ By doping into the HAp lattice and utilizing the polydopamine coating structure, along with the thermally stimulated copper release effect, Cu can be synergistically achieved. 2+ The slow, prolonged release of copper promotes tissue repair, inhibits bacterial growth, and induces angiogenesis and bone tissue growth. The synergy between the thermal response of copper and the excellent photothermal response of polydopamine achieves superior thermal response, thereby enhancing the local immune system response and generating thermal stimulation to promote the production of copper ions (Cu). 2+ The material exhibits various effects, including copper doping and polydopamine coating. The combination of copper doping and polydopamine coating synergistically achieves excellent biocompatibility. The polydopamine coating also enhances the adhesion between the material and bone tissue, as well as Ca-P deposition and mineralization on the bone surface. Furthermore, an optimal combination of copper doping and polydopamine coating can achieve a balance of excellent biocompatibility (98% cell viability), photothermal response performance, and the slow release of a specific concentration of Cu. 2+ And maintain for a relatively long time, Cu 2+ The release concentration can reach 14.2 ppm, preferably 20-100 ppm, and remain for more than 72 hours, preferably more than a week, so that the material can exert a better heat-responsive antibacterial effect and induce angiogenesis and bone tissue growth, thereby better promoting tissue repair for the treatment of chronic bone infection defects.

[0026] (2) In this invention, copper-doped hydroxyapatite is first prepared, preferably under acidic conditions. Then, the ratio of copper-doped hydroxyapatite to dopamine solution is controlled to prepare polydopamine-coated copper-doped hydroxyapatite. The resulting polydopamine-coated copper-doped hydroxyapatite material exhibits excellent photothermal response, good biocompatibility, and can slowly and for a long time release Cu. 2+ Cu 2+ The release concentration can reach 14.2 ppm or higher, preferably 20-100 ppm, and remain for more than 72 hours, preferably more than a week. This is beneficial for tissue repair, has an antibacterial effect, and induces angiogenesis and bone tissue growth. Attached Figure Description

[0027] Figure 1 XRF analysis of Comparative Examples 1, 2 and Examples 1-5.

[0028] Figure 2 Infrared images of copper-doped hydroxyapatite prepared in Comparative Example 1 and Examples 1, 3, and 5.

[0029] Figure 3 The XRD pattern of copper-doped hydroxyapatite was prepared in Example 3.

[0030] Figure 4 Photothermal images of copper-doped hydroxyapatite were obtained for Comparative Example 1 and Examples 1, 3, and 5.

[0031] Figure 5 SEM-EDS were performed on copper-doped hydroxyapatite in Comparative Example 1 and Examples 1, 3, and 5.

[0032] Figure 6 Biocompatibility diagrams of copper-doped hydroxyapatite prepared in Comparative Example 1 and Examples 1-5.

[0033] Figure 7 Infrared images of copper-doped hydroxyapatite coated with polydopamine were obtained for Comparative Example 3 and Examples 6, 7, and 9.

[0034] Figure 8 Photothermal images of copper-doped hydroxyapatite were obtained for Comparative Example 3 and Examples 6, 7, and 9.

[0035] Figure 9 SEM-EDS analysis was performed on copper-doped hydroxyapatite in Comparative Example 4 and Examples 6, 7, and 9.

[0036] Figure 10 Biocompatibility diagrams of copper-doped hydroxyapatite prepared for Comparative Examples 3 and 4 and Examples 6-9.

[0037] Figure 11 The copper ion release curves are for Comparative Example 3 and Example 7. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0039] It should also be noted that, in order to avoid obscuring the invention with unnecessary details, only structures and / or processing steps closely related to the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted. Furthermore, it should be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.

[0040] This invention provides a copper-doped hydroxyapatite coated with polydopamine, which consists of copper-doped hydroxyapatite and polydopamine coated on the surface of copper-doped hydroxyapatite. In the copper-doped hydroxyapatite, copper replaces calcium and is doped into the HAp lattice. The amount of copper doping is 1% to 10% by mass percentage, that is, copper accounts for 1-10 wt% of the total mass of copper and calcium in the copper-doped hydroxyapatite.

[0041] As a further improvement of the present invention, hydroxyapatite (HAp) exhibits a nanoscale rod-like structure (10-40 nm wide and 30-200 nm long), and the copper doping content is preferably 1%-5%, more preferably 3%-5%.

[0042] As a further improvement of the present invention, polydopamine is formed on the surface of copper-doped hydroxyapatite by oxidative self-polymerization of dopamine to obtain copper-doped hydroxyapatite coated with polydopamine, wherein the mass ratio of copper-doped hydroxyapatite to dopamine is 1:1 to 1:0.01, and the reaction conditions are: high-speed stirring at room temperature in the dark for 8 to 24 hours.

[0043] As a further improvement of the present invention, the mass ratio of copper-doped hydroxyapatite to dopamine is preferably 1:0.1 to 1:0.01, more preferably 1:0.05 to 1:0.01, and even more preferably 1:0.05 to 0.02.

[0044] As a further improvement of the present invention, the copper content in the coated polydopamine-doped copper hydroxyapatite material is 3% to 5%, and the mass ratio of copper-doped hydroxyapatite to dopamine is 1:0.05 to 1:0.02.

[0045] As a further improvement of the present invention, the temperature rise of the coated polydopamine-doped copper hydroxyapatite material can be controlled within 3 to 35°C by adjusting the polydopamine coating ratio.

[0046] As a further improvement of the present invention, the copper ion release concentration of the coated polydopamine-doped copper hydroxyapatite material of the present invention can reach 14.2 ppm or higher, more preferably 20-100 ppm, and can be maintained for more than 72 hours, and most preferably more than one week. The present invention also provides a method for preparing the above-mentioned coated polydopamine-doped copper hydroxyapatite material, characterized by comprising the following steps:

[0047] S1. Prepare copper-doped hydroxyapatite for later use;

[0048] S2. The copper-doped hydroxyapatite obtained in step S1 is mixed with a dopamine solution at a preset mass ratio. Polydopamine is formed on the surface of the copper-doped hydroxyapatite by oxidative self-polymerization of dopamine, thereby obtaining copper-doped hydroxyapatite coated with polydopamine.

[0049] The preparation method of copper-doped hydroxyapatite in step S1 includes the following steps: preparing calcium chloride and copper chloride dihydrate solutions for later use; preparing diammonium hydrogen phosphate solutions for later use; stirring and heating the prepared calcium chloride and copper chloride dihydrate solutions to 80-85°C, then adding acid to adjust the pH of the system to 3-5, and stirring thoroughly to obtain a mixed solution; adding the prepared diammonium hydrogen phosphate solution dropwise to the above-obtained reaction solution, mixing according to the preset (Ca+Cu) / P ratio, and stirring for 2-4 hours; then adding ammonia water dropwise to the reaction solution to adjust the pH to about 9-11, and continuing to stir for 0.5-1.5 hours, turning off the stirring and heating, and allowing the reaction solution to stand and age for at least 12 hours; collecting the precipitate, washing it repeatedly, then drying it at 50-100°C to constant weight, grinding and sieving to obtain copper-doped hydroxyapatite (CuHAp).

[0050] As a further improvement of the present invention, in step S1, the molar ratio is 1.65≤Ca / P≤1.82.

[0051] As a further improvement of the present invention, in step S2, the mass ratio of copper-doped hydroxyapatite to dopamine is 1:1 to 1:0.01, and the reaction conditions are: high-speed stirring at room temperature in the dark for 8 to 24 hours; the preparation method of the coated polydopamine-doped copper hydroxyapatite includes the following steps: preparing a Tris solution and adjusting the pH value to 8.0 to 9.5 with dilute hydrochloric acid for later use; adding dopamine to the prepared Tris solution and mechanically stirring at room temperature in the dark until the solution turns black for later use; adding copper-doped hydroxyapatite to the above-obtained reaction solution and mixing according to the mass ratio of copper-doped hydroxyapatite to dopamine of 1:1 to 1:0.01, and stirring at room temperature in the dark for 8 to 24 hours; collecting the precipitate, washing repeatedly, then freeze-drying, grinding and sieving to obtain coated polydopamine-doped copper hydroxyapatite (PDAx@CuHAp).

[0052] As a further improvement of the present invention, in step S1, the concentration of calcium ions in the calcium salt solution is 0.05-0.5 mol / L, the concentration of copper ions in the copper salt solution is 0.01-0.1 mol / L, and the concentration of phosphate ions in the phosphate salt solution is 0.03-0.35 mol / L.

[0053] As a further improvement of the present invention, in step S2, the mass ratio of copper-doped hydroxyapatite to dopamine is 1:0.1 to 1:0.01, more preferably 1:0.05 to 1:0.01, and even more preferably 1:0.05 to 0.02.

[0054] The following describes the coated polydopamine-doped copper hydroxyapatite material and its preparation method provided by the present invention with reference to specific embodiments.

[0055] Example 1

[0056] This embodiment provides a method for preparing copper-doped hydroxyapatite material, including the following steps:

[0057] S1. Weigh 21.98g of anhydrous calcium chloride and 0.22g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0058] S2. Weigh 16.01g of diammonium hydrogen phosphate and add a certain amount of purified water. The ratio of the mass of diammonium hydrogen phosphate to the mass of purified water is 1:20.

[0059] S3. Slowly add the diammonium hydrogen phosphate solution obtained in step S2 to the mixed solution described in step S1. Continue stirring at 135 r / min for 3 hours at 85°C. Then, add ammonia water dropwise to adjust the pH to approximately 9-11, and continue stirring for another hour. Turn off heating and stirring, and allow to stand for at least 12 hours. Discard the supernatant, collect the precipitate, filter under positive pressure, and wash repeatedly with purified water. Dry the precipitate at 60°C to constant weight, grind, and sieve to obtain copper-doped hydroxyapatite powder (CuHAp-1).

[0060] Example 2

[0061] The difference from Example 1 is that the amount of raw materials used in step S1 is changed, while other conditions remain the same as in Example 1. Specifically:

[0062] S1. Weigh 21.53g of anhydrous calcium chloride and 0.67g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0063] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 h. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another h. The heating and stirring are turned off, and the mixture is allowed to stand for at least 12 h. The supernatant is discarded, the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain copper-doped hydroxyapatite powder (CuHAp-2).

[0064] Example 3

[0065] The difference from Example 1 is that the amount of raw materials used in step S1 is changed, while other conditions remain the same as in Example 1. Specifically:

[0066] S1. Weigh 21.09g of anhydrous calcium chloride and 1.11g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0067] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 h. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another h. The heating and stirring are turned off, and the mixture is allowed to stand for at least 12 h. The supernatant is discarded, the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain copper-doped hydroxyapatite powder (CuHAp-3).

[0068] Example 4

[0069] The difference from Example 1 is that the amount of raw materials used in step S1 is changed, while other conditions remain the same as in Example 1. Specifically:

[0070] S1. Weigh 20.42g of anhydrous calcium chloride and 1.78g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0071] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 h. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another h. The heating and stirring are turned off, and the mixture is allowed to stand for at least 12 h. The supernatant is discarded, the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain copper-doped hydroxyapatite powder (CuHAp-4).

[0072] Example 5

[0073] The difference from Example 1 is that the amount of raw materials used in step S1 is changed, while other conditions remain the same as in Example 1. Specifically:

[0074] S1. Weigh 19.98g of anhydrous calcium chloride and 2.22g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0075] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 h. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another h. The heating and stirring are turned off, and the mixture is allowed to stand for at least 12 h. The supernatant is discarded, the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain copper-doped hydroxyapatite powder (CuHAp-5).

[0076] Comparative Example 1

[0077] The difference from Example 1 is that the amount of raw materials used in step S1 is changed, while other conditions remain the same as in Example 1. Specifically:

[0078] S1. Weigh 22.2g of anhydrous calcium chloride, add a certain amount of purified water, the mass ratio of anhydrous calcium chloride to purified water is 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add dilute hydrochloric acid to adjust the pH of the system to 3-5, and stir thoroughly to obtain a mixed solution;

[0079] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 hours. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another hour. Heating and stirring are turned off, and the mixture is allowed to stand for at least 12 hours. The supernatant is discarded, and the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain hydroxyapatite powder (HAp).

[0080] Table 1. Mass ratios of anhydrous calcium chloride and copper chloride dihydrate corresponding to Examples 1-5 and Comparative Example 1.

[0081]

[0082] Comparative Example 2

[0083] The difference from Example 5 is that the reaction environment in step S1 is changed, while other conditions remain the same as in Example 5. Specifically:

[0084] S1. Weigh 19.98g of anhydrous calcium chloride and 2.22g of copper chloride dihydrate, add a certain amount of purified water, the total mass of anhydrous calcium chloride and copper chloride dihydrate: the mass of purified water = 1:20, add the solution to the reaction vessel, stir mechanically and heat to 85℃, then add sodium hydroxide solution, adjust the pH of the system to 9~10, and stir thoroughly to obtain a mixed solution;

[0085] S2. The diammonium hydrogen phosphate solution obtained in step S2 of Example 1 is slowly added dropwise to the mixed solution described in step S1. The reaction is continued at 85°C with stirring at 135 r / min for 3 h. Then, ammonia water is added dropwise to adjust the pH value to about 9-11, and the reaction is continued with stirring for another h. The heating and stirring are turned off, and the mixture is allowed to stand for at least 12 h. The supernatant is discarded, the precipitate is collected, filtered under positive pressure, and washed repeatedly with purified water. The precipitate is dried at 60°C to constant weight, ground, and sieved to obtain copper-doped hydroxyapatite powder (CuHAp-0).

[0086] Examples 6-9

[0087] This embodiment provides a method for preparing a polydopamine-coated copper-doped hydroxyapatite material, comprising the following steps:

[0088] S1. Select the copper-doped hydroxyapatite (CuHAp-3) prepared in Example 3 for later use;

[0089] S2. Prepare a 10mM Tris solution and adjust the pH to about 8.5 with dilute hydrochloric acid for later use.

[0090] S3. Add dopamine to the prepared 10mM Tris solution and mechanically stir at room temperature in the dark until the solution turns black. Add copper-doped hydroxyapatite to the above-obtained reaction solution and mix at a mass ratio of 1:0.1 to 1:0.01 of copper-doped hydroxyapatite to dopamine. Stir at high speed at room temperature in the dark for 12 hours. Collect the precipitate, wash it repeatedly, freeze-dry it, grind it and sieve it to obtain copper-doped hydroxyapatite coated with polydopamine.

[0091] Comparative Examples 3 and 4

[0092] CuHAp-3 described in Example 3 was selected as Comparative Example 3.

[0093] The difference between Comparative Example 4 and Examples 6-9 is that the mass ratio of copper hydroxyapatite and dopamine in step S3 is changed. The corresponding mass ratios of copper hydroxyapatite and dopamine in Examples 6-9 and Comparative Examples 3 and 4 are shown in Table 2.

[0094] Table 2 shows the mass ratio of copper-doped hydroxyapatite to dopamine in Examples 6-10.

[0095]

[0096]

[0097] Example 10

[0098] The difference from Example 7 is that step S1 is changed to use copper-doped hydroxyapatite (CuHAp-2) prepared in Example 2 to prepare the PDA. 0.02 @CuHAp-2, other conditions are the same as in Example 7, and will not be repeated here.

[0099] Figure 1 XRF analysis was performed on Comparative Examples 1 and 2 and Examples 1-5. The results showed that the actual Cu doping amount under acidic conditions was close to the theoretical value; however, the actual Cu doping amount (1.71 ± 0.17%) under alkaline conditions was much lower than the theoretical value (10%). This indicates that the doping conditions affect Cu doping, and the acidic conditions of pH 3-5 in this invention are more conducive to Cu doping into HAp crystals.

[0100] Figure 2 Infrared spectra of Comparative Example 1 and Examples 1, 3, and 5. 3572 cm⁻¹ -1 and 1637cm -1 The absorption peaks are attributed to the vibrational peaks of OH. These peaks are observed at 564, 600, 632, and 960 cm⁻¹. -1 A distinct absorption peak was observed, which is attributed to PO4. 3-Bending and tensile vibrations of PO. The characteristic peaks of the functional groups of HAp appeared in all modified HAp groups. When the copper doping amount increased from 1% to 5%, CuHAp-3 showed a higher peak at 1093 cm⁻¹ compared to CuHAp-1. -1 and 1032cm -1 The absorption peak at this point exhibited a significant stretching vibration, which is attributed to the vibrational peak that occurs after Ca is replaced by Cu. This demonstrates the successful preparation of copper-doped hydroxyapatite.

[0101] Figure 3 The XRD characterization results of CuHAp-3 prepared in Example 3 are shown. The results show that the characteristic peaks of the prepared CuHAp-3 are consistent with the standard card (PDF#09-0432), indicating that Cu doping did not have a significant impact on the crystal structure of HAp.

[0102] Figure 4 Near-infrared irradiation temperature rise diagrams (808 nm, 0.5 W / cm²) for Comparative Example 1 and Examples 1, 3, and 5. 2 (Irradiation for 5 minutes). The results showed that, with Cu... 2+ Increasing the doping amount endows the material with certain photothermal absorption properties; when the Cu doping amount gradually increases to 10%, the material heats up the fastest, and the temperature can reach 43.7℃ in 5 minutes.

[0103] Comparative Example 1 and Examples 1, 3, and 5 were characterized by SEM-EDS. The results are as follows. Figure 5 As shown, the prepared hydroxyapatite (HAp) exhibits a nanoscale rod-like structure (10–40 nm wide and 30–200 nm long). When the Cu doping concentration is 1% to 5%, irregular fragment-like material accumulation can be observed on the surface of the CuHAp rod-like structure. As the Cu doping concentration gradually increases to 10%, it can be observed that this rod-like structure is gradually completely covered by a large amount of irregular fragment-like material accumulation, and the surface fragment structure is more tightly connected into a single piece, resulting in a significant change in surface morphology.

[0104] Figure 6 To assess the biocompatibility of Comparative Example 1 and Examples 1-5, the results showed that the cytotoxicity of the material gradually increased with increasing Cu ion doping concentration. When the Cu content increased to 10%, the toxicity of the material increased significantly, and the cell viability decreased significantly to below 58%.

[0105] Figure 7 Infrared spectra of Comparative Example 3 and Examples 6, 7, and 9. 3572 cm⁻¹ -1 and 1637cm -1 The absorption peaks are attributed to the vibrational peaks of OH. All sample groups show absorption peaks at 563, 602, 632, and 962 cm⁻¹. -1 A distinct absorption peak was observed, which is attributed to PO4.3- Bending and tensile vibrations of PO. With increasing PDA coating concentration, at 1093 cm⁻¹... -1 and 1032cm -1 The absorption peak at this point exhibits stretching vibrations. This indicates that PDA has been coated on the surface of CuHAp, and that the coating of polydopamine does not have a significant impact on the functional groups and structure of CuHAp.

[0106] Figure 8 Near-infrared irradiation temperature rise diagrams (808 nm, 0.5 W / cm²) for Comparative Example 3 and Examples 6, 7, and 9. 2 (Irradiation for 5 min). The results showed that the photothermal absorption performance of the material was significantly enhanced with the increase of PDA coating concentration; when the mass ratio of copper-doped hydroxyapatite to dopamine was 1:0.1, the temperature reached a maximum of 69.5℃ after 5 min.

[0107] Comparative Example 4 and Examples 6, 8, and 9 were characterized by SEM-EDS, and the results are as follows: Figure 9 As shown, the copper-doped hydroxyapatite coated with polydopamine exhibits a rod-like structure, but a certain amount of particulate matter (polydopamine) accumulates on the material surface. The more polydopamine is coated, the more particulate matter accumulates, indicating that polydopamine was successfully coated on the surface of the copper-doped hydroxyapatite.

[0108] Figure 10 To compare the biocompatibility of Examples 3, 4, and Examples 6-9, the results showed that appropriate PDA coating can improve the cytotoxicity of the materials. Copper-doped hydroxyapatite coated with dopamine exhibited better compatibility, particularly at a mass ratio of 1:0.1 to 1:0.01, and especially 1:0.05 to 1:0.01, with a cell viability exceeding 90%, preferably reaching 95% (when the mass ratio of copper-doped hydroxyapatite to dopamine was 1:0.01 to 1:0.05), and up to 98% (when the mass ratio of copper-doped hydroxyapatite to dopamine was 1:0.02). This indicates that coating with a certain amount of dopamine can significantly improve the biocompatibility of Cu. 2+ The toxicity is significant. However, when the mass ratio of copper-doped hydroxyapatite to dopamine is 1:1, the toxicity of the material increases significantly and the cell survival rate drops significantly to below 60%.

[0109] Take 50 mg of the prepared sample and place it in 10 mL of purified water. After standing at room temperature for 24 h, take 100 μL and measure the Cu content using inductively coupled plasma atomic emission spectrometry (ICP). 2+ The release amount. Then, it was measured at 808nm, 0.5W / cm. 2 After NIR irradiation for 20 min, 100 μL of the sample was taken and measured using inductively coupled plasma atomic emission spectrometry (ICP) to obtain Cu. 2+The release amount. Repeat the above operation at set intervals to measure Cu. 2+ The amount released.

[0110] Figure 11 The figures show the copper ion release curves for Comparative Example 3 and Example 7. Figure 11 As shown: The samples of Comparative Example 3 and Example 7 were placed at room temperature for 24 hours, Cu 2+ The release concentration was only about 10 ppm. After being excited by near-infrared light irradiation for the same amount of time with the same near-infrared power, the Cu in Comparative Example 3 showed a significantly lower release concentration. 2+ The release rate is not very significant, and it takes a relatively long time to reach a release level of over 15 ppm. Example 7 Cu 2+ The release can rapidly reach over 20 ppm, and can maintain a release level of over 20 ppm for a relatively long time without continuous near-infrared irradiation (up to approximately 100 ppm of Cu). 2+ The release of Cu can last for more than a week. The figure shows the Cu release after being placed at room temperature for 24 hours, then excited by near-infrared light, with an interval of 2 36 hours.

[0111] The PDA0.02@CuHAp-2 sample of Example 10 was placed at room temperature for 24 hours, and Cu 2+ The release concentration was approximately 5 ppm after intermittent near-infrared irradiation (808 nm, 0.5 W / cm²). 2 After two 20-minute NIR irradiations, the concentration can reach above 14.2 ppm and remain for a long time, at least 72 hours.

[0112] The results showed that, under the same near-infrared power irradiation and the same time, Cu dopamine-coated copper-doped hydroxyapatite... 2+ The release rate is significantly accelerated, Cu 2+ The release concentration can rapidly reach 14.2 ppm, and can further reach over 20 ppm. Therefore, we can regulate the release concentration of Cu by controlling the power of the near-infrared light and the duration of illumination. 2+ Release amount. It can release copper ion concentrations of 14.2 ppm or higher, preferably 20-100 ppm, and maintain this concentration for more than 72 hours, and ideally for more than a week.

[0113] The specific advantages of this invention are as follows:

[0114] This invention utilizes copper ions (Cu) 2+ Copper-doped hydroxyapatite, combined with polydopamine coating, yields a polydopamine-coated copper-doped hydroxyapatite material exhibiting excellent photothermal response, good biocompatibility, and the ability to slowly and continuously release Cu. 2+ It is beneficial for tissue repair, has an antibacterial effect, and induces angiogenesis and bone tissue growth.

[0115] In this invention, Cu is used 2+ By doping into the HAp lattice and utilizing the polydopamine coating structure, along with the thermally stimulated copper release effect, Cu can be synergistically achieved. 2+ The slow, prolonged release of copper promotes tissue repair, inhibits bacterial growth, and induces angiogenesis and bone tissue growth. The synergy between the thermal response of copper and the excellent photothermal response of polydopamine achieves superior thermal response, thereby enhancing the local immune system response and generating thermal stimulation to promote the production of copper ions (Cu). 2+ The material exhibits various effects, including copper doping and polydopamine coating. The combination of copper doping and polydopamine coating synergistically achieves excellent biocompatibility. The polydopamine coating also enhances the adhesion between the material and bone tissue, as well as Ca-P deposition and mineralization on the bone surface. Furthermore, an optimal combination of copper doping and polydopamine coating can achieve a balance of excellent biocompatibility (98% cell viability), photothermal response performance, and the slow release of a specific concentration of Cu. 2+ (Cu 2+ The release concentration can reach 14.2 ppm, preferably 20-100 ppm, and remain for more than 72 hours, preferably more than one week, enabling the material to exert a better heat-responsive antibacterial effect and induce angiogenesis and bone tissue growth, thereby achieving better promotion of tissue repair for treatment such as repair of chronic bone infection defects.

[0116] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A polydopamine-coated copper-doped hydroxyapatite material, characterized in that: It is composed of copper-doped hydroxyapatite and polydopamine coated on the surface of copper-doped hydroxyapatite. In the copper-doped hydroxyapatite, copper replaces calcium and is doped into the HAp lattice. The amount of copper doping is 1% to 10% by mass percentage.

2. The polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: Copper-doped hydroxyapatite exhibits a nanoscale rod-like structure, with a width of 10–40 nm and a length of 30–200 nm, and the copper doping content is 1%–5%.

3. The polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: Polydopamine was formed on the surface of copper-doped hydroxyapatite using an oxidative self-polymerization method to obtain copper-doped hydroxyapatite coated with polydopamine. The mass ratio of copper-doped hydroxyapatite to dopamine was 1:1 to 1:0.

01. The reaction conditions were: high-speed stirring at room temperature in the dark for 8 to 24 hours.

4. The polydopamine-coated copper-doped hydroxyapatite material according to claim 3, characterized in that: The mass ratio of copper-doped hydroxyapatite to dopamine is 1:0.1 to 1:0.

01.

5. The polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: The copper content in the polydopamine-coated copper-doped hydroxyapatite material is 3% to 5%, and the mass ratio of copper-doped hydroxyapatite to dopamine is 1:0.05 to 1:0.

02.

6. The polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: By adjusting the proportion of polydopamine coating, the temperature rise of the polydopamine-coated copper-doped hydroxyapatite material after near-infrared irradiation can be controlled within the range of 3–35°C.

7. The polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: The copper ion release concentration can reach over 14.2 ppm and can be maintained for over 72 hours.

8. A method for preparing the polydopamine-coated copper-doped hydroxyapatite material according to claim 1, characterized in that: Specifically, the steps include the following: S1. Prepare copper-doped hydroxyapatite for later use; S2. The copper-doped hydroxyapatite obtained in step S1 is mixed with a dopamine solution at a preset mass ratio. Polydopamine is formed on the surface of the copper-doped hydroxyapatite by oxidative self-polymerization of dopamine, thereby obtaining copper-doped hydroxyapatite coated with polydopamine.

9. The method for preparing the polydopamine-coated copper-doped hydroxyapatite material according to claim 8, characterized in that: In step S1, the preparation method of copper-doped hydroxyapatite includes the following steps: preparing calcium chloride and copper chloride dihydrate solutions for later use; preparing diammonium hydrogen phosphate solutions for later use; stirring and heating the prepared calcium chloride and copper chloride dihydrate solutions to 80-85°C, then adding acid to adjust the pH of the system to 3-5, and stirring thoroughly to obtain a mixed solution; adding the prepared diammonium hydrogen phosphate solution dropwise to the above-obtained reaction solution, mixing according to the preset (Ca+Cu) / P ratio, and stirring for 2-4 hours; then adding ammonia water dropwise to the reaction solution to adjust the pH to about 9-11, and continuing to stir for 0.5-1.5 hours, turning off the stirring and heating, and allowing the reaction solution to stand and age for at least 12 hours; collecting the precipitate, washing it repeatedly, then drying it at 50-100°C to constant weight, grinding and sieving to obtain copper-doped hydroxyapatite.

10. The method for preparing the coated polydopamine-doped copper hydroxyapatite material according to claim 8, characterized in that: In step S1, the molar ratio is 1.65 ≤ Ca / P ≤ 1.

82. The preparation method of the coated polydopamine-doped copper hydroxyapatite in step S2 includes the following steps: preparing a Tris solution and adjusting the pH to 8.0–9.5 with dilute hydrochloric acid; adding dopamine to the prepared Tris solution and mechanically stirring at room temperature in the dark until the solution turns black; adding copper-doped hydroxyapatite to the above-obtained reaction solution and mixing at a mass ratio of 1:1 to 1:0.01 (copper-doped hydroxyapatite to dopamine), and stirring at high speed at room temperature in the dark for 8–24 hours; collecting the precipitate, washing repeatedly, then freeze-drying, grinding, and sieving to obtain coated polydopamine-doped copper hydroxyapatite.

Citation Information

Patent Citations

  • An ultra-micro silver-doped hydroxyapatite coating, its preparation method and application

    CN105664251B